Emotional Dysregulation, Hopelessness and Dysmorphophobic Concerns Among Hospitalized Patients with Autoimmune, Inflammatory, and Metabolic Skin Disorders - Tonia Samela; Giorgia Cordella; Valeria Antinone; Maria Beatrice Pupa; Alessandra Vendoni Capitani; Dario Didona; Luciana Di Girolamo; Anna Rita Giampetruzzi; Damiano Abeni (Behavioral Sciences)
Chronic disfiguring skin conditions profoundly affect patients’ quality of life (QoL) due to their physical, psychological, and emotional consequences. Although the presence of depression and anxiety symptomatology in dermatological patients is well established, the specific roles of emotional dysregulation, dysmorphophobic concerns, and hopelessness in this population require further investigation. This study aimed for the following: (1) to assess symptoms of emotional dysregulation, dysmorphophobic concerns, and hopelessness in hospitalized patients with severe dermatological diseases; (2) analyze whether emotional dysregulation mediates the relationship between dysmorphophobic concerns and hopelessness. A cross-sectional study was conducted with 120 hospitalized dermatology patients. Patients completed standardized measures, including the Emotional Dysregulation Scale (EDs), Beck Hopelessness Scale (BHS), and the Questionario sul Dismorfismo Corporeo “Body Dysmorphic Disorder Questionnaire” (QDC). Disease severity and pain perception were assessed using the Physician Global Assessment (PGA) and the Numerical Rating Scale (NRS). Significant associations were observed between emotional dysregulation, dysmorphophobic concerns, and hopelessness. Emotional dysregulation partially mediated the relationship between dysmorphophobic concerns and hopelessness (indirect effect: b = 0.013, CI [0.004, 0.026]). Higher dysmorphophobic concerns were associated with emotional dysregulation, which, in turn, predicted greater hopelessness. Emotional dysregulation seems to play a critical role in the relationship between dysmorphophobic concerns and hopelessness in dermatological patients.